Gamma Rays Induced Modification in Ultrahigh Molecular Weight Polyethylene (UHMWPE). (8th June 2021) - Aarya, Suveda; Kumar, Pawan; Bhatia, Mamta; Kumar, Sanjeev; Sharma, Jyotsna; Siddhartha,
Abstract : Modifications taking place in ultrahigh molecular weight polyethylene (UHMWPE) films due to gamma ray radiation-induced and investigated in correlation with the applied doses. Films were irradiated in a vacuum at room temperature by a 1.25 MeV Co 60 a source with doses ranging from 0 to 300 kGg. The optical, chemical, structural, and surface morphological properties of the irradiated and unirradiated UHMWPE films were investigated by UV-Visible, FTIR, XRD, and SEM, respectively. The band gap E g decreases with increasing radiation dose and coloration effects have been seen at higher doses. FTIR spectra show an oscillatory behavior in the transmittance intensities without affecting in their peak positions. Number of small absorption peaks can be seen clearly which may be due to the cross-linking of the polymeric chain. No significant change in crystalline peak has been found in the X-ray diffraction pattern indicating the structural stability of the polymer. The morphology of the smooth topography of the polymer samples to change rougher one polymeric sample shows the formation of microvoids on the surface of the polymeric materials with the increase of the doses from 0 to 300 kGy.